Infrano / Muhammad Harith Mohd Norbi and Norarifah Ali - Mohd Norbi, Muhammad Harith; Ali, Norarifah (Faculty of Art and Design, 2021)
Since the pandemic , the whole world fell into a sudden phase of displeasure following up with the new norms that forces people to wear masks and use hand sanitizers as frequently as ever. There is also social distance where people have to keep their distance with other people at least 1 meter to avoid the spread of the Covid-19 Virus. More people are becoming afraid of going out in public as even a slight touch of an object that could be exposed to the Covid-19 Virus could possibly infect you and the community that you live in, including your family and friends that are relatively close to you. The Ministry of Health of Malaysia (MOH) has ordered a strict Standard Operating Procedure (SOP) following these events to control the vast spread of the Covid-19 Virus. Infrano is a wearable device that enables users to detect whether the people surrounding them have symptoms of Covid-19 infections. One of the most noticeable out of the many symptoms of Covid-19 infections is that the infected often has an increased of body temperature above normal and mostly they will catch a fever. This is one of the main points of developing this product. During the development of designing Infrano the researcher has pointed out that it is significant since one of the factors of symptoms with Covid-19 infection will encourage the public to become more trusting of the product idea. One of the features of Infrano is that it can scan the temperature of the user itself and it can also scan the temperature of the people surrounding them within the range of 5 meters apart from the device itself. This is due to the fact that one of the Standard Operating Procedures (SOP) of shops and public places is that they require people to either write their personal information for contact or scanning the QR code distributed to every shop and scan their temperature before entering these premises .